2010
DOI: 10.1637/8729-032409-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Infection with H5 Subtype Influenza Virus in Apparently Healthy Local Chickens in Kaduna State, Nigeria

Abstract: A serologic survey for antibodies against H5 subtype influenza virus in 605 apparently healthy local chickens using a hemagglutination inhibition test was carried out in 12 local government areas of Kaduna state, Nigeria. An overall prevalence of 18.1% was recorded, with a higher prevalence of 27.3% in six local government areas that have not reported outbreaks of highly pathogenic avian influenza (HPAI) H5N1 virus and a lower prevalence of 7.5% in six local government areas that had reported and confirmed out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The study confirms that radio was a major means of HPAI information dissemination like previous studies though unlike local poultry farmers, television was also an appropriate medium of HPAI information for dog owners [6,25]. This is because unlike local poultry farmers, dog owners are more affluent and can afford TV and generators if there is power failure.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The study confirms that radio was a major means of HPAI information dissemination like previous studies though unlike local poultry farmers, television was also an appropriate medium of HPAI information for dog owners [6,25]. This is because unlike local poultry farmers, dog owners are more affluent and can afford TV and generators if there is power failure.…”
Section: Discussionsupporting
confidence: 79%
“…However, AI currently has a worldwide distribution in many domestic and wild animals including pigs, dogs and humans but chickens, quails and turkeys are the most susceptible [2,3]. The outbreak of HPAI H5N1 in Nigeria in 2006 increases the risk of introduction and spread of the virus in other domestic animals especially with reports of avian influenza virus and antibodies in apparently healthy waterfowls and chickens in Northern Nigeria and Kaduna State respectively [4,5,6]. These extensively raised domestic animals with minimal or no biosecurity, are at risk of exposure to AI viruses from direct contact with infected wild birds or indirect contact with fomites [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the large number of laying birds in individual flocks as compared to other chicken types under these sectors. This significantly affected the economy not only because a whooping sum of N631 million (US$5.43 million) was paid as compensations to farmers [ 19 ] but also because laying hens contribute huge resources to the national poultry flock and this emphasizes the importance of commercial layer flocks [ 20 ] for Nigeria's economy. It was also observed that the average mortality rate was the least in commercial layers (11.11%) and the highest in broilers (73.92).…”
Section: Discussionmentioning
confidence: 99%
“…Proximity to other poultry farms would imply not only the mixing with other birds, infected but apparently healthy, but also the potential exchange of equipment. The role of backyard farms in the spread of HPAI H5N1 was expressed as a concern not only in Egpyt, Vietnam, Cambodia (Hosny, 2006; Burgos et al., 2008a,b), but also in Nigeria (Joannis et al., 2008) where a cross‐sectional study in the State of Kaduna estimated that 18.1% of apparently healthy chicken were serologically positive to H5 virus (Durosinlorun et al., 2010). In the Mekong Delta in Vietnam, flocks sharing scavenging areas with flocks from other farms were at an increased risk of HPAI outbreak (Henning et al., 2009).…”
Section: Discussionmentioning
confidence: 99%